Magmatic pulses of the Tatun Volcano Group, northern Taiwan, revisited: Constraints from zircon U-Pb ages and Hf isotopes. (November 2018) - Chu, Mei-Fei; Lai, Yu-Ming; Li, Qiuli; Chen, Wen-Shan; Song, Sheng-Rong; Lee, Hao-Yang; Lin, Te-Hsien
Highlights: Magmatism in northern Taiwan started from ∼3 Ma. Keelungyu erupted ∼0.4 Ma as part of the Tatun Volcano Group (TVG). The TVG landscape was mainly shaped <0.8 Ma, particularly ≤0.35 Ma. Abstract: The initiation and duration of magmatism in the Tatun Volcano Group (TVG), likely resulting from extensional collapse of the northern Taiwan mountain belt, remains an important issue of debates in the Taiwan orogeny. Here we report a detailed study of U-Pb ages determined by SIMS and LA-ICPMS, together with Hf isotopic data, of zircon separates from a total of 22 extrusive rocks from the TVG lava flow and additional two andesites from Keelungyu (KLY), a volcanic islet off NE Taiwan. Magmatic zircons from the TVG are characterized by uniform and high Hf isotopic ratios, with εHf (T) mostly from +20 to +10. Their overall 206 Pb/ 238 U ages suggest that the TVG magmatism was initiated ∼3 Ma but more active ≤0.8 Ma with a flare up ≤0.35 Ma. Magmatic zircons from the two KLY samples reveal identical 206 Pb/ 238 U ages (0.41 Ma), coupled with Hf isotopes [εHf (T): +25 to +9] comparable to those of the TVG. Thus, KLY is proposed as part of the TVG. Consequently, we argue that the main body of the TVG formed ≤0.8 Ma by post-collisional volcanism, but the mechanism resulting in the magmatic episodes ≥1.0 Ma remains obscure due to the scarcity of rock exposures.